THE EFFECT OF CAREER DEVELOPMENT AND ALLOWANCES ON WORK DISCIPLINE WITH ORGANIZATIONAL COMMITMENT AS A MEDIATING VARIABLE: EVIDENCE FROM THE BPSDM SECRETARIAT - Dian Haerani; Zainul Kisman (Jurnal Ilmiah Mahasiswa Ekonomi Syariah (JIMESHA), 2026)
This study aims to examine the effect of career development and allowances on work discipline with organizational commitment as a mediating variable in the context of the BPSDM Secretariat. A quantitative approach was employed using a survey method, and data were collected from 77 employees, including civil servants and government contract employees. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that career development and allowances have significant positive effects on organizational commitment, but do not have significant direct effects on work discipline. Organizational commitment is found to have a significant effect on work discipline. Furthermore, the mediation analysis indicates that organizational commitment fully mediates the relationships between career development and work discipline as well as between allowances and work discipline. These findings suggest that improvements in career development programs and allowance systems will not automatically enhance work discipline unless they are able to strengthen employees’ organizational commitment. This study highlights the central role of organizational commitment as a key mechanism linking human resource practices to disciplined work behavior in public sector organizations. The results provide practical implications for managers and policymakers in designing more effective human resource policies to improve employee discipline through strengthening organizational commitment